Territorial and maritime disputes in the West Philippine Sea foreign policy choices and their impact on domestic stakeholders - Baviera, Aileen S. P. (Public policy)
Foreign policy decision-making typically involves an interplay between domestic and international actors and interests. Using Philippine policy in the West Philippine Sea as a case, this study looks at who the domestic stakeholders are, the effects of the maritime disputes on them, and their role in foreign policy choices made by the Aquino government. The study examines the defense and maritime law enforcement sector, the fisheries sector and energy industry, as well as those engaged in trade, investments, and tourism cooperation with China. Among certain security sector stakeholders, there were perceptions that the arbitration or legal approach was over-emphasized at possible cost to short-term security goals. Fishing and energy stakeholders also felt there was not much support from government, and that interactions initiated by the government were for the purpose of gathering understanding and support for policy and to institute stop-gap solutions, rather than to address problems that arose as consequences of the disputes or of foreign policy decisions. The study recommends better inter-agency harmonization of its policy priorities, improving central-local governments' understanding of their respective roles, and introducing more consultative and inclusive decision-making processes involving non-state stakeholders, in order to improve policy coherence. Apart from defense of sovereignty and territorial integrity, development diplomacy based on domestic stakeholders' interests and needs should be placed front and center of the next stage of Philippine statecraft on the West Philippine Sea issue, whether through bilateral negotiations with China or regional cooperation of both. Law and diplomacy will remain instruments rather than ends in themselves, and the objectives of our foreign policy will remain security of the state, welfare of the people, peace in the region.